La política migratoria mexicana después de IRCA - Alba, Francisco (El Colegio de México A.C., 1999)
The responses given by Mexico, particularly its government, to the issue of Mexican immigration to the United States, have become more important since the changes in US immigration legislation, initiated in 1986 and updated in 1996, and following the intensification of the immigrant and xenophobic demonstrations carried out by large sectors of American society. This paper briefly reviews Mexican policies implemented when the Bracero programs ended and provides a more detailed analysis of how government policies changed from the 1986 Immigration Reform and Control Act (IRCA) to the more recent 1996 Illegal Immigration Reform and Immigrant Responsibility Act, exploring some of the implications of these changes and Mexico's current migration policy.